A Project-Based Learning Student Worksheet Based on STEM and Green Chemistry to Improve Students’ Conceptual Understanding and 21st Century Competencies - Hidayah, Hayyu; Wardani, Sri; Sumarni, Woro (Universitas Negeri Semarang, 2025)
This article is a narrative review that discusses the development and implementation of a student worksheet based on Project-Based Learning (PjBL) integrated with the STEM (Science, Technology, Engineering, and Mathematics) approach and the principles of Green Chemistry to enhance students’ conceptual understanding and 21st century competencies. Today’s education faces the challenge of not only focusing on content mastery but also equipping students with critical thinking, problem-solving, collaboration, communication, creativity, and awareness of global environmental issues. The integration of PjBL with STEM and Green Chemistry offers a relevant and contextual solution for meaningful chemistry learning. This review analyzes national and international studies published between 2020 and 2025, showing that the use of worksheets based on this integrated approach can improve students’ learning engagement, deepen conceptual understanding, and foster 21st century skills. Moreover, incorporating Green Chemistry principles into learning contributes significantly to instilling values of sustainability and environmental responsibility from an early age. This article also recommends further development and empirical research to test the effectiveness of such worksheets in various educational contexts, particularly in secondary school chemistry instruction.